Is procreative beneficence obligatory? - Saunders, Ben (Journal of medical ethics, 2015)
Julian Savulescu defends the principle of procreative beneficence, according to which parents have a prima facie moral obligation to choose the child with the best expected life. In this paper, I argue that Savulescu fails to show that procreative beneficence is genuinely obligatory, because of his equivocation between moral reason and moral obligation. Savulescu assumes that morality requires us to do what we have most (moral) reason to do, but many deny this, for instance because they believe we have reasons (but no obligation) to perform supererogatory actions. Even if parents have moral reasons to choose the child with the best expected life, they may not be under any obligation to do so.